IMPLEMENTASI MANAJEMEN STRATEGIK UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI MIN 5 SRAGEN - Adawiyah, Rabiatul; Kurniawan; Abdurrohman, Asep; Amirullah, Febry; Hasan, Haslindah; Halid, Sri Julyarti; Herwanita; Husriah (JURNAL KAJIAN ISLAM MODERN, 2024)
The quality of education of an institution cannot be separated from the Strategic Management implemented. MIN 5 Sragen is one of the schools under the auspices of the Ministry of Religion in Sragen Regency, Central Java which has good quality of education. Therefore, this study was conducted with the aim of 1) analyzing the implementation of Strategic Management that has been carried out by MIN 5 Sragen 2) determining the effect of the implementation of Strategic Management on the quality of education at MIN 5 Sragen. This study is a descriptive qualitative study conducted with various data collection techniques such as closed questionnaires, in-depth interviews, and observations. The resulting data were analyzed using an interactive method initiated by Miles and Huberman. The results of the study indicate that MIN 5 Sragen has implemented strategic management through six stages, namely 1) formulation of the school's vision and mission; 2) analysis of the internal environment; 3) analysis of the external environment; 4) analysis and determination of goals, objectives, and strategic planning; 5) implementation of strategic management; and 6) evaluation of strategic management. Each stage has been implemented well so that MIN 5 Sragen is able to reap the benefits of implementing strategic management.